Assessment of the Transmission’s Impact on the Operational Properties of Land Vehicles - I. Nekrasov, V.; A. Ziganshin, R.; V. Ziganshina, A.; S. Zakharov, N.; N. Shpitko, G. (International Journal of Engineering and Technology, 2018)
The article considers the issue of the transmission's effect on the operational properties of the land vehicles. The main transmission parameters are given in the work. The analysis of the possibilities of using different types of transmission is shown. The technique for selecting the number of gears and the mean value of the capacity utilization factor is considered. The technical and economic assessment is given on the basis of complex factors of the specific productivity of the road train and the prime cost of its use.Â Â